If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1010) = 3(x + -10101) Reorder the terms: 4(1010 + x) = 3(x + -10101) (1010 * 4 + x * 4) = 3(x + -10101) (4040 + 4x) = 3(x + -10101) Reorder the terms: 4040 + 4x = 3(-10101 + x) 4040 + 4x = (-10101 * 3 + x * 3) 4040 + 4x = (-30303 + 3x) Solving 4040 + 4x = -30303 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4040 + 4x + -3x = -30303 + 3x + -3x Combine like terms: 4x + -3x = 1x 4040 + 1x = -30303 + 3x + -3x Combine like terms: 3x + -3x = 0 4040 + 1x = -30303 + 0 4040 + 1x = -30303 Add '-4040' to each side of the equation. 4040 + -4040 + 1x = -30303 + -4040 Combine like terms: 4040 + -4040 = 0 0 + 1x = -30303 + -4040 1x = -30303 + -4040 Combine like terms: -30303 + -4040 = -34343 1x = -34343 Divide each side by '1'. x = -34343 Simplifying x = -34343
| 44-x=11 | | n+3.7=9.8 | | 2-5[x+3(x+7)]= | | 7x-31=-25 | | 8.5t=83.30 | | 4x-0=1 | | -23682-6k=6+18k | | 6x(x-9)=13x^2-55x | | 10x+7=-x-15 | | 5x=234 | | 8z=9z-3 | | 7+3t-1=8t+24-2t | | 2[4-9x]=9x+7 | | -143=3(-6b-1)+4 | | 6(5y-8)-(7y+4)= | | 9x^2+13=247 | | -4(1-5v)=-144 | | 7+5[1+2(2x+5)]=6(x+7) | | P-16=13-6p | | 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 | | .50(x-2)=4x-0.2222x-4 | | 5(3b-4)=40 | | 3(4x+3)=17 | | 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 | | F(x)=x^3+2x^2+x+4 |